Analisis Kesulitan Belajar Peserta Didik dalam Memahami Materi Pembelajaran Kimia Kelas XI MIA SMA - Pane, Eva Pratiwi; Sauduran, Golda Novatrasio; Simanjuntak, Bernard; Lampola Sitorus P.; Pasaribu, Sunggul (PendIPA Journal of Science Education, 2025)
Many high school students consider chemistry to be a difficult subject. Most students still have difficulty understanding chemical concepts comprehensively, but the obstacles they experience have not been fully identified by teachers. Chemistry is one of the subjects that is less favored by students, because science, especially chemistry, is studied abstract things. Students' difficulties in learning chemistry result in many students experiencing failure in learning chemistry material. This study aims to describe and explain various learning difficulties and the factors causing difficulties in learning chemistry experienced by high school students. This study involved 44 students from all grades XII MIA and one chemistry teacher as the subjects. This study used a phenomenological research type with a qualitative approach. The data collection process was carried out using document study methods, observation, questionnaires, and interviews. Based on the results of the study, the level of student learning difficulties is categorized as slightly difficult (43%), quite difficult (48%), and difficult (9%). Internal factors that cause learning difficulties include a lack of understanding of chemistry material, low mathematical ability, and minimal motivation in learning chemistry. External factors that influence learning difficulties include the teacher's teaching methods, the negative impact of socializing with peers, and less conducive learning situations and times.